Adopting a craft approach in the context of social innovation. Issue 2 (1st September 2017) - Bofylatos, Spyros
This article explores the value of adopting a craft-based approach in design for social innovation in the wider context of design for sustainability. The main position is that services are products of a craft process. By looking at the results of the processes of social innovation (services) and craft (craft artefacts), the shared characteristics of these two very different processes and results point towards a plethora of shared characteristics that could be leveraged. At the same time the common discourse between service design and social innovation provides a fertile ground for the ongoing debate about eco-modernism and radical approaches to sustainability. Synthesizing parts of craft into social innovation cross-pollinates both fields and opens up a robust theoretical background for service design while providing a platform for craft as redirective practice to further move towards sustainment. Craft in this context is understood as a future-oriented, post-industrial way of designing. These two fields of application of designerly ways of thinking complement each other on many different levels and from a theoretical point of view provide a path towards a sustainable future. Finding new ways of synthesizing the two and communicating the underlying, alternative system of values formed between them is part of the transition necessary to avoid the environmental and social catastrophes that we are marching towards.